Reproductive choices: a qualitative study of Dutch Moroccan and Turkish consanguineously married women's perspectives on preconception carrier screening - Petra Verdonk; Suzanne Metselaar; Oka Storms; Edien Bartels (BMC, 2018)
Abstract Background Cousin marriages, in the Netherlands most frequently between Turkish or Moroccan couples, are at higher risk of having offspring with recessive disorders. Often, these couples not perceive or accept this risk, and it is hardly considered a reason to refrain from family marriages. Preconception carrier screening (PCS) is offered to Jewish groups, and more recently in the Netherlands, to genetically isolated communities. In this study, Dutch Moroccan and Turkish women's perspectives on preconception carrier screening (PCS) and reproductive choices were explored. Methods Individual interviews were held with Dutch Turkish and Moroccan consanguineously married women (n = 10) and seven group discussions with Turkish and Moroccan women (n = 86). Transcripts and notes were analyzed thematically. Results All women welcomed PCS particularly for premarital genetic screening; regardless of possible reproductive choices, they prefer information about their future child's health. Their perspectives on reproductive choices on the basis of screening results are diverse: refraining from having children is not an option, in vitro fertilization (IVF) combined with pre-implantation genetic diagnosis (PGD) was welcomed, while prenatal genetic diagnosis (PND), termination of pregnancy (TOP), in vitro fertilization with a donor egg cell, artificial insemination with donor sperm (AID), and adoption, were generally found to be unacceptable. Besides, not taking any special measures and preparing for the possibility of having a disabled child are also becoming optional now rather than being the default option. Conclusions The women's preference for PCS for premarital screening as well as their outspokenness about not marrying or even divorcing when both partners appear to be carriers is striking. Raising awareness (of consanguinity, PCS and the choice for reproductive options), and providing information, screening and counseling sensitive to this target group and their preferences are essential in the provision of effective health care.